2018
DOI: 10.1111/jocd.12767
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen plasma skin regeneration for the treatment of mild‐to‐moderate periorbital wrinkles: A prospective, randomized, controlled evaluator‐blinded trial

Abstract: Nitrogen plasma skin regeneration is effective and safe for the treatment of mild-to-moderate periorbital wrinkles and darkening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Skin healing after nitrogen PSR treatment involves a process of natural skin regeneration, wherein the upper/ outer layers of skin that are desiccated during treatment remain intact as a natural biological dressing during the early phase of healing; as the "old" skin desquamates, the newly regenerated and smoother pink skin appears [13]. Clinical benefits of nitrogen PSR treatment include a range of treatment protocols for diverse skin types and conditions, effective reversal of photodamage and dyschromia, preservation of natural skin tone, and modest reduction of acne scarring and rhytidosis [10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Skin healing after nitrogen PSR treatment involves a process of natural skin regeneration, wherein the upper/ outer layers of skin that are desiccated during treatment remain intact as a natural biological dressing during the early phase of healing; as the "old" skin desquamates, the newly regenerated and smoother pink skin appears [13]. Clinical benefits of nitrogen PSR treatment include a range of treatment protocols for diverse skin types and conditions, effective reversal of photodamage and dyschromia, preservation of natural skin tone, and modest reduction of acne scarring and rhytidosis [10,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen PSR histological studies (porcine, human) showed significant neo‐collagenesis and a corresponding reduction in elastosis in the upper dermis . Clinical evaluation of nitrogen PSR treatment effectiveness demonstrated benefits in the appearance of treated skin with improvements in dyschromia, photodamage and skin texture including reduction of acne scarring and rhytidosis . Complications resulting from nitrogen PSR treatment include focally delayed healing, post‐inflammatory hyperpigmentation, and rare hypertrophic scarring events .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple treatments of PSR have been proven to be clinically effective for traumatic scars, mesh skin-grafted scars, and wrinkles at an interval of 3 weeks to 1 month. 9,16 In this study, we reported single-dose PSR treatment combined with radiotherapy as an effective management for keloids. The endpoint of PSR therapy was when the lesions were almost as flat as the surrounding normal skin although red in color.…”
Section: Discussionmentioning
confidence: 94%